A Novel Allotriploid Hybrid Derived From Female Goldfish × Male Bleeker’s Yellow Tail - Wang, Jing; He, Weiguo; Wang, Wen; Luo, Ziye; Han, Linmei; Xiang, Caixia; Chai, Mingli; Li, Tangluo; Li, Jihong; Luo, Kaikun; Zhao, Rurong; Liu, Shaojun (Frontiers in Genetics, 2022)
Breeding of new varieties is one of the main directions in aquaculture. And hybridization, especially distant hybridization, is a traditional and effective breeding method. In this study, goldfish (Carassius auratus, GF, 2n = 100) and Bleeker's yellow tail (Xenocypris davidid bleeker, YT, 2n = 48) which belong to different subfamilies were crossed each other. In the reciprocal crosses, the female GF × male YT successfully generated surviving offspring (GFYT). While the female YT × male GF was lethal and all the embryos stopped developing before the neurula stage. All GFYT possessed 124 chromosomes (3n = 124) with two sets from GF and one set from YT. The measurable and countable traits of GFYT were identified. The genetic characteristics of 5S rDNA were also revealed. There were respectively four and three different 5S rDNA types in GF (assigned as GF-Ⅰ~Ⅳ) and YT (assigned as YT-Ⅰ~Ⅲ), and GFYT specifically inherited YT-Ⅰ and YT-Ⅱ 5S rDNA types from YT, GF-Ⅲ and GF-Ⅳ from GF. In addition, there were only testis-like and fat-like gonads were found in GFYT. Interestingly, in the testis-like gonads, spermatids presented pyknotic and heteromorphous chromatin and invaginated cell membrane, no mature sperm were found. Further TUNEL assays indicated apparent apoptotic signals mainly distributed around spermatid regions, and the expression of apoptosis pathway-related genes including p53, bcl-2, bax and caspase9 were significantly up-regulated. Moreover, the expression of meiosis related genes including spo11, dmc1 and rad51 showed an abnormally high level, but mns1 and meig1, two key genes involving the maturation of spermatid, were extremely down-regulated. In brief, this study not only produced a novel and sterile allotriploid hybrid, but also revealed the genetic characteristics of 5S rDNA and the possible causality of the spermatogenesis dysfunctions, providing new insights into the mechanisms underlying polyploidization and sterility resulting from distant hybridization.